2020
DOI: 10.1016/j.resglo.2020.100018
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 pandemic on micro, small, and medium-sized Enterprises operating in Pakistan

Abstract: The outbreak of coronavirus disease (COVID-19) has severely affected the global and Pakistani economy. Major victims of the COVID-19 outbreak are micro, small, and medium-sized enterprises (MSMEs). This article aims to assess the impact of COVID-19 outbreak on these businesses and provide policy recommendations to help MSMEs in reducing business losses and survive through the crisis. We adopted an exploratory methodology with comprehensively reviewing the available literature, including policy documents, resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
549
2
26

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 564 publications
(606 citation statements)
references
References 31 publications
29
549
2
26
Order By: Relevance
“…Given that natural calamities have often forced national and global economies into depression, there is great need for advance planning as well as disaster preparedness not only for governments but for the business enterprises too. Between 1998 and 2017, the number of natural calamities has massively shot up, during which a sum of $2.9 trillion direct economic losses have been posted by affected countries (World Trade Organization, 2019;Shafi et. al., 2020).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Given that natural calamities have often forced national and global economies into depression, there is great need for advance planning as well as disaster preparedness not only for governments but for the business enterprises too. Between 1998 and 2017, the number of natural calamities has massively shot up, during which a sum of $2.9 trillion direct economic losses have been posted by affected countries (World Trade Organization, 2019;Shafi et. al., 2020).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic has seriously disrupted capital chains, leading to a decrease in R&D investment (Shafi, Liu, and Ren 2020) which adversely affects financing activities. Therefore, we believe that R&D investment needs to be increased for enterprises to meet their technological demands, inappropriate investments in R&D due to the pandemic may fail to induce enterprises to carry out technological innovation (Ma, Hou, and Tian 2019), as natural disasters often exacerbate poor allocation decisions (Dasanayaka and Wedawatta 2014).…”
Section: Theory Developmentmentioning
confidence: 99%
“…These small industries are worse affected and people are even starving to death due to COVID-19. Shafi et al (2020) collected and analyzed online survey data from 184 Pakistani SMEs, which showed that most businesses were severely affected by COVID-related restrictive measures. Among the problems faced by SMEs there are financial problems, supply chain disruption, decreased demand, reduced sales and profits.…”
Section: Covid-19 and The Current Situation In Pakistanmentioning
confidence: 99%